Biosynthesis of Se-methyl-seleno-l-cysteine in Basidiomycetes fungus Lentinula edodes (Berk.) Pegler - Klimaszewska, M. (Springerplus, 2016)
BACKGROUND: The aim of the current study was to investigate whether the Basidiomycetes fungus Lentinula edodes can biosynthesize Se-methyl-seleno-l-cysteine, a seleno-amino acid with strong anticancer activity, and to optimize the culture conditions for its biosynthesis. We hypothesize that preparations obtained from Se-methyl-seleno-l-cysteine-enriched mycelia from this medicinal mushroom would possess stronger cancer-preventive properties than current preparations. RESULTS: By optimizing the concentration of selenium in the culture medium, we increased the mycelial concentration of Se-methyl-seleno-l-cysteine from essentially non-detectable levels to 120 µg/g dry weight. Significantly elevated levels of this amino acid also correlated with significant (twofold) inhibition of mycelial growth. Increases in the concentration of mycelial Se-methyl-seleno-l-cysteine appeared to be highly correlated with the enhanced biosynthesis of selenomethionine and total selenium content in mycelium. CONCLUSIONS: We have demonstrated that in L. edodes, enhanced biosynthesis of this non-protein amino acid eliminates excess selenium.